BENEATH THE FLAVOUR: UNVEILING THE CARCINOGENIC RISK FROM CONSUMPTION OF DRIED FISH– A SYSTEMATIC REVIEW - S, SHAAFIYA FATHIMA; PRABU D; MUTHULAKSHMI S; SINDHU R; DINESH DHAMODHAR; RAJMOHAN M; LUBNA FATHIMA; RAGAVAPRIYA E (The Bioscan, 2026)
Aim and Background: Dried fish is widely consumed as an affordable, nutrient-rich protein source with a long shelf life, particularly in developing regions. However, traditional drying and smoking practices can introduce hazardous contaminants, including aflatoxins, polycyclic aromatic hydrocarbons (PAHs), heavy metals, and fungal toxins, many of which possess carcinogenic potential. Poor hygiene, open-air drying, and improper storage further exacerbate microbial growth and toxin accumulation, raising significant public health concerns. This systematic review aims to evaluate the major contaminants in dried fish and their associated carcinogenic risks. Materials and Methods: A systematic review was conducted in accordance with PRISMA guidelines. Electronic databases including PubMed, ScienceDirect, Cochrane Library, ResearchGate, and Google Scholar were searched for English-language, peer-reviewed studies published from 1990 onwards. Eligible studies assessed chemical or biological contamination in dried fish or examined associations between dried fish consumption and cancer risk. Of 300 records screened, 34 full-text articles were assessed, and 4 studies met the inclusion criteria. Results: All included studies reported contamination linked to carcinogenic risk. Aflatoxin B1, a Group 1 carcinogen, was detected in up to one-third of samples. Heavy metals such as cadmium, lead, and mercury frequently exceeded permissible limits, while smoked fish showed higher PAH concentrations. Epidemiological evidence indicated an increased lung cancer risk among frequent consumers (OR ≈ 2.83), with children exhibiting the highest estimated lifetime cancer risk. Conclusion: Improperly processed or stored dried fish represents a potential source of dietary carcinogen exposure. Strengthened regulation, improved processing practices, and public awareness are urgently required to protect public health while preserving the cultural importance of dried fish.